WEAP21 based modelling under climate change considerations for a semi-arid region in southern-central Chile - Duque, Luis; Vázquez, Raúl (Maskana, 2017)
The water balance of an irrigation project in the Chilean semi-arid zone was modelled using the WEAP21 code. A combined deterministic/stochastic protocol was applied for defining the hydrological prediction intervals of the model. Climate Change potential implications on the useful life of the irrigation project (year 2070) were predicted considering the variability in precipitation and temperature forecasts. Thereto, it was considered the scenario A1B of the 2007 Intergovernmental Panel on Climate Change report, generated by the Regional Climate Model PRECIS-ECHAM, specially developed for Chilean conditions. The study revealed that most of the inspected hydrological model parameters are insensitive to model predictions and the associated simulation limits may be categorized as acceptable. Nevertheless, the structure of WEAP21 had difficulties representing low flows because of the apparent inability to mimic the complex hydro-physical characteristics of the shrink-swell granitic soils which are predominant in the study basin. Even though the original Climate Change projections (CChP) of the RCM were refined, using observations of the historical period, it is important to underline that significant uncertainties may remain and as such the current results should be handled with care. With respect to historical records, mean annual climate forecasts suggest a maximum temperature increment of about +1.1oC and a maximum reduction in precipitation of 20.7%. The hydrological modelling suggests a maximum reduction in the mean annual streamflow of 49.7% and a reduction in the magnitude and frequency of streamflow peaks. Bearing in mind the potential uncertainties attached to CChP, the irrigation project will most probably be significantly affected in terms of water availability and crop water consumption since rainfall is expected to decrease and temperature, and as such evapotranspiration, to increase.